On Becker’s Theory of Commitment: An Empirical Verification Among Blue-Collar Workers - Baba, Vishwanath; Jamal, Muahammad (Relations industrielles / Industrial Relations, 1979)
The present study attempts to assess the empirical relevance of Becker's theory of commitment to study organizational commitment among blue collar workers. The relative importance of demographic, background and job factors as possible predictors of organizational commitment are examined. The sample is drawn from packaging, power distribution and manufacturing industries in Canada. Stepwise multiple regression analysis is used to isolate the important predictors of organizational commitment.